Palavras, psique e pandemia: discursos sobre sonhos durante o surto de Covid-19 no Brasil - Soares, Flávio (2025)
At the beginning of century XXI, due to a traumatic event that present us a global health crisis and a far-right government that ascends the power, we observe beyond individual and collective traumas, a sequence of statements about dreams that passed in Brazil. This way, according to the production of conditions, and considering the emergency of these statements, this research intends to identify, select, describe and interpret what it is said and the ways of saying about this object. To better exposure the aims of this work, it should be added that the study in question has a perspective: i: draw a speech panorama about dreams in different production conditions in the long historical duration, in order identify what is preserved, it resumes, updates, develops, and transforms, into similar statements produced in Brazil during the COVID 19 pandemic.; ii. to understand the discursive processes of statements about materialized dreams during the coronavirus outbreak, aiming to verify whether they reproduce, reformulate (in various ways: as of additions, omissions, inflections, etc.), or erase discourses about dreams produced under historical and social conditions of trauma; iii. Describe, and interpret some statements in their relationships with the emotions in speeches about materialized dreams in Brazil in the pandemic period to signal the presence and agency of sensations and emotions in discourse, phenomena central to the constitution of subjects and meaning, particularly in discursive production tied to collective trauma. For so much, this study uses the theoretical and methodological foundations of Speech analysis, from Foucault's discursive studies and the "new" historiographical currents, as sensitivity of History. As for the results, we basically observe how the experience of dreaming, the dream narrative and the interpretation of this phenomenon, as well as its senses, values and functions, they are closely linked to historical, politics and social events, in other words, we see how, in different social formations, the discourses about dreams are build, updated, resumed, transformed and silenced. Especifically, during the pandemic time, we saw how certain speeches authorized some subjects, considered qualified entering the order of speech and take a position of contemporary dream interpreters; we learn how she/woman , health professionals, and teachers general population and health/education workers, they formed a privileged group of dreamers; and we identify how in exceptional times, certain leaders can penetrate dreamlike productions to represent power relations, the struggles and systems of domination of a certain social formation. Finally, we learned how certain speeches about dreams highlighted the affections and/or states of fear, destitution, depression, and happiness.